Peningkatan Pemahaman Hak Dasar Anak bagi Orang Tua di Tangerang: Program Kolaborasi dengan KemenPPPA - Helsa; Legita, Fathima Eunike; Setyantoro, Gloria Eirene (Devotion : Jurnal Pengabdian Psikologi, 2024)
Violence and exploitation of children in Indonesia remain serious issues, as indicated by data from the Online Information System for the Protection of Women and Children (Simfoni PPA), which recorded 15,120 cases of child violence in 2023. Based on that, it is very necessary to fulfill children's basic rights, as stated in the 1989 Convention on the Rights of the Child. This Community Service Program (PkM) is a collaboration between Yayasan Mandiri Kreatif Indonesia (Yamakindo), the Ministry of Women's Empowerment and Child Protection (KemenPPPA), and the Faculty of Psychology at Pelita Harapan University (UPH). The program, themed "Healthy Parenting by Upholding Children's Fundamental Rights", aims to educate 20 parents in the Tangerang area on children's rights and effective parenting strategies. The activities involved lectures, a Q&A session, and puppet interactions, accompanied by pre-test and post-test evaluations. The results indicated an increase in parents' understanding of children's rights. Although the program was well-executed, improvements in time management and the implementation of follow-up programs for continuous monitoring and evaluation are recommended for future initiatives.